2018
DOI: 10.1111/andr.12483
|View full text |Cite
|
Sign up to set email alerts
|

Adipose‐derived stem cells improve erectile function partially through the secretion of IGF‐1, bFGF, and VEGF in aged rats

Abstract: Adipose-derived stem cells (ADSCs) have recently been considered as a promising therapy for erectile dysfunction (ED). However, the mechanism of ADSC-based therapy is unclear. Insulin-like growth factor-1 (IGF-1), basic fibroblast growth factor (bFGF), and vascular endothelial growth factor (VEGF) secreted by ADSCs were assessed in vitro. Sixteen 24-month-old male Sprague-Dawley rats were used for comparative analysis of 2-week treatment with labeled ADSCs or PBS. Eight additional 5-month-old rats were used as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(49 citation statements)
references
References 49 publications
1
48
0
Order By: Relevance
“…Volatile O 2 − is produced during cellular respiration by the mitochondria and NOX enzymes during tissue inflammation; O 2 − is eliminated by SOD which catalyzes its conversion to H 2 O 2 . Antioxidant effects of MSC treatments have been associated with enhanced SOD activity or the expression of SODs in models of aging, age‐related erectile dysfunction, chemotherapy‐induced pulmonary fibrosis or gonadotoxicity colitis, pancreatitis, septic lung injury, arthritis, hepatotoxicity and hepatic ischemia reperfusion injury, Alzheimer's disease, and ovarian autografts 33,34,37,38,43,50,62‐70 . MSCs secrete all isoforms of SOD including SOD1 and SOD2, which are archetypically not released extracellularly 33,59,71,72 .…”
Section: Antioxidative Mechanisms Of Mscsmentioning
confidence: 99%
“…Volatile O 2 − is produced during cellular respiration by the mitochondria and NOX enzymes during tissue inflammation; O 2 − is eliminated by SOD which catalyzes its conversion to H 2 O 2 . Antioxidant effects of MSC treatments have been associated with enhanced SOD activity or the expression of SODs in models of aging, age‐related erectile dysfunction, chemotherapy‐induced pulmonary fibrosis or gonadotoxicity colitis, pancreatitis, septic lung injury, arthritis, hepatotoxicity and hepatic ischemia reperfusion injury, Alzheimer's disease, and ovarian autografts 33,34,37,38,43,50,62‐70 . MSCs secrete all isoforms of SOD including SOD1 and SOD2, which are archetypically not released extracellularly 33,59,71,72 .…”
Section: Antioxidative Mechanisms Of Mscsmentioning
confidence: 99%
“…Kinins contribute to the reduction of oxidative stress by increasing the synthesis of nitric oxide (NO) and prostaglandin (PGs) (Kayashima et al, 2012). Several studies have established that oxidative stress plays an important role in the pathophysiological process of erectile dysfunction, and previously we showed that the levels oxidative stress in aged rats were significantly higher than in young rats (Yang et al, 2018). Increasing oxidative stress may drive the PI3K/AKT/ mTOR signaling pathway, resulting in the activation of mTOR.…”
Section: Discussionmentioning
confidence: 99%
“…We have con rmed that the BM-MSCs modi ed with shIGFBP-3 still retain their original characteristics, such as multidirectional differentiation potential and proliferation capacity in vitro. Producing some bioactivity factors may contribute to the therapeutic effects in vivo [28]. A paracrine action rather than the differentiation of stems cells may play a major role in the e cacy of stem cell transplanltion.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Yang. et al [28] revealed that ADSCs can improve erectile function through the secretion of cavernous IGF-1, bFGF, and VEGF in old rats. This study indicated that BM-MSCs alone, especially BM-MSCs modi ed with shRNA targeting IGFBP-3 treatment can improve aging-related ED partially owing to the secretion of IGF-1 and VEGF.…”
Section: Discussionmentioning
confidence: 99%